Primary fallopian tube cancer in the setting of endometriosis - Pandey, Deeksha; Bhalla, Varun; Mittal, Anushri; Shetty, Jyothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We report the first case of PFTC arising in the setting of pelvic endometriosis. A 45 year old nulliparous lady, menopausal lady presented with pelvic mass. She had history of pelvic endometriosis. MRI findings were suggestive of ovarian malignancy. Histological analysis of specimen obtained following staging laparotomy proved it to be a case of bilateral PFTC. She received 6 cycles of adjuvant chemotherapy. This case opens a new door to think or investigate if fallopian tube endometrioma behaves as a more aggressive premalignant lesion. This case also poses questions whether it is important to differentiate an endometrioma arising from the ovary to one which is arising from a fallopian tube. Once identified can fallopian tube endometrioma also be managed medically or should it be always removed surgically?